2015
DOI: 10.1016/j.bbamem.2015.04.013
|View full text |Cite
|
Sign up to set email alerts
|

How do voltage-gated sodium channels enhance migration and invasiveness in cancer cells?

Abstract: Voltage-gated sodium channels are abnormally expressed in tumors, often as neonatal isoforms, while they are not expressed, or only at a low level, in the matching normal tissue. The level of their expression and their activity is related to the aggressiveness of the disease and to the formation of metastases. A vast knowledge on the regulation of their expression and functioning has been accumulated in normal excitable cells. This helped understand their regulation in cancer cells. However, how voltage-gated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 93 publications
1
84
0
1
Order By: Relevance
“…There is growing evidence that cancer cell hallmarks are strongly regulated by ion channels including K + [5], [6], [7], Ca 2+ [8], [9], [10], and Na + channels [11], [12]. In particular, several channels including transient receptor potential (TRP) channels are implicated in molecular mechanisms of the metastatic cascade [4].…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence that cancer cell hallmarks are strongly regulated by ion channels including K + [5], [6], [7], Ca 2+ [8], [9], [10], and Na + channels [11], [12]. In particular, several channels including transient receptor potential (TRP) channels are implicated in molecular mechanisms of the metastatic cascade [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, multiple studies have recently demonstrated their expression in non-excitable cells, in which they regulate cellular functions such as migration, differentiation, endosome acidification, phagocytosis and podosome formation15. In addition, Na V are abnormally expressed in carcinoma cells and tumour biopsies, and their activity is associated with aggressive features and cancer progression161718. Expression of the Na V 1.5 isoform in breast tumours is correlated with metastases development and patients' death1920.…”
mentioning
confidence: 99%
“…TTX, tetrodotoxin sensitive; SCN5A, gene that encodes Na v 1.5; SCN9A, gene that encodes Na v 1.7; VGSCs, voltage-gated sodium channels. Source: Besson et al (2015), Driffort et al (2014), Nelson, Yang, Dowle, Thomas, and Brackenbury (2015), Patel and Brackenbury (2015), and Roger et al (2015).…”
Section: Human-sw480mentioning
confidence: 98%